A very thin tube shaped like a quarter of a toroid has one end attached to the origin $(0,0,0)$ and the other end at $(R,0,R)$. Determine its center of mass.

So obviously $y_G = 0$. Using Pappus theorem, we may determine $x_G$ by rotating the tube around the z-axis, giving half a sphere with radius $R$. The surface area is $A = 2 \pi R^2$ and the length of the arc $l$ is $R\pi/2$ (quarter of a circle) so we get $x_G = A/(2\pi l) = \frac{2\pi r^2}{2\pi R\pi/2} = 2R/\pi$.

Now to the tricky part, determining $z_G$. Rotating the arc around the x-axis renders a surface area that can be calculated using the formula $A = 2 \pi \int f(x) \sqrt{1+f'(x)^2} dx $. We can express the arc in terms of $z$ and $x$ as $$z(x) = \sqrt{R^2 - x^2}$$ giving $f'(x)^2 = \frac{x^2}{R^2-x^2}$. Thus the area is: $$A = 2\pi \int_{0}^{R} \sqrt{R^2-x^2} \sqrt{1+\frac{x^2}{R^2-x^2}} dx $$ $$= 2 \pi \int_{0}^{R} \sqrt{\frac{(R^2-x^2)(R^2-x^2+x^2)}{R^2-x^2}} dx$$ $$= 2\pi \int_{0}^{R} |R| dx = 2 \pi R^2 $$ Again, using Pappus theorem to obtain $z_G$, we get $$z_G = A/(2\pi l) = \frac{2\pi R^2}{2 \pi R \pi/2} = 2R/\pi$$

This is however is wrong! According to the book, $z_G = R - \frac{2R}{\pi}$. What did I do wrong?


A better and convenient solution to this question would be this (In case it is not compulsory to use Pappus theorem)

Image is self explanatory. I prefer using the X-Y coordinates as shown.

Image is self explanatory. I prefer using the X-Y coordinates as shown. Thesecan be converted to match the question later.

Center of mass in any dimension is given by $$x_{CM}=\dfrac{\int x\,dm}{\int dm}$$

By symmetry, the centre of mass lies on the Y axis. $$x_{CM}=0$$ $$y_{CM}=\dfrac{\int^{3\pi/4}_{\pi/4}\lambda R^2\sin\theta\,d\theta}{\int^{3\pi/4}_{\pi/4}\lambda R\,d\theta}\implies R \dfrac{[-\cos\theta]^{3\pi/4}_{\pi/4}}{[\theta]^{3\pi/4}_{\pi/4}}\implies \dfrac{2\sqrt{2}R}{\pi}$$

Therefore, $\dfrac{2\sqrt{2}R}{\pi}$ is the distance from the center of the arc (located at $(R, 0, 0)$) along a line making $135^{\circ}$ with positive X-axis in the question's coordinate system. Thus, $$x_G=R-[\dfrac{1}{\sqrt{2}}\times\dfrac{2\sqrt{2}R}{\pi}]\implies\dfrac{(\pi-2)R}{\pi}$$ $$z_G=\dfrac{1}{\sqrt{2}}\times\dfrac{2\sqrt{2}R}{\pi}\implies\dfrac{2R}{\pi}$$

I guess you somehow interchanged $x_G$ and $z_G$. Hope this helps and I made no calculation errors!


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.